PERAN MOTIVASI DAN MINAT DALAM PERILAKU PEMBERIAN ASI EKSKLUSIF TENAGA KEPERAWATAN TANGERANG SELATAN - Mustikawati (Journal Prima Health Science, 2020)
Exclusive breastfeeding for 6 months is very important according to one of the objectives of the MillenniumDevelopment Goals (MDGs) of reducing child mortality and improving maternal health. Based on the report by theWorld Breastfeeding Trends Initiative 2012, Indonesia was ranked 49 out of the 51 countries that support exclusivebreastfeeding. Nurses have a very important role especially educative and promotion to the public in providing healtheducation on exclusive breastfeeding. The purpose of this study was to analyze factors associated with the behavior ofexclusive breastfeeding in the hospital Nurses in South Tangerang region. This study used cross sectional approach, iethe measurement of independent variables and the dependent variable only one at a time. The results of the bivariateanalysis using Chi-square statistical test with the results of research knowledge, level of education, motivation, andsupport the family does not have a significant relationship with the behavior of exclusive breastfeeding in nursingpersonnel with P value respectively: P = 0.069; P = 0.476; P = 0.079 ; P = 0.153 ;. While interest has a significantrelationship with the behavior of exclusive breastfeeding in the hospital nursing staff South Tangerang region, with a Pvalue in a row is P = 0.049 with OR: 3.400.